Pengaruh Volatilitas Harga Kopi Terhadap Ekspor di Indonesia - virda zikria (Jurnal Agriuma, 2020)
One of the plantation crops that are the mainstay of Indonesian economy is coffee plant, however the coffee plant is prone to harvest failure, so the price of coffee in the world market is very volatile and will ultimately affect the price of coffee in the domestic market. Price fluctuations also occur as a result of supply and demand behavior which can create a risk of price uncertainty or price volatility. This research is important to do to determine the coffee price fluctuations and coffee price volatility. This study also aims to determine the effect of coffee price volatility on coffee exports from Indonesia. The data used are secondary time series data with historical volatility methods with cointegration testing methods and Error Correction Model (ECM). The development of coffee price volatility in Indonesia in 2010-2019 tended to be unstable so that it could be categorized as having high price volatility. The volatility of coffee prices and coffee exports in Indonesia has an inverse relationship in the long term and in the short term. This is based on the acquisition of cointegration test results which show a negative coefficient value, which means that if the value of coffee price volatility in Indonesia increases, the volume of coffee exports in Indonesia will decline.Keyword: coffee; price; export; volatility